Dissolution, Solubility, and Stability of the Basic Ferric Sulfate-Arsenates [Fe(SO4)x(AsO4)y(OH)z·nH2O] at 25–45°C and pH 2–10. (7th June 2021) - Zhu, Zongqiang; Yang, Hongqu; Liu, Jie; Zhu, Yinian; Tang, Shen; Zhang, Lihao; Wang, Xingxing
Abstract : Basic ferric sulfate-arsenates [FeSAsOH, Fe(SO4 )x (AsO4 )y (OH)z ·nH2 O] were prepared and characterized to study their potential fixation of arsenic in the oxidizing and acidic environment through a dissolution for 330d. The synthetic solids were well-shaped monoclinic prismatic crystals. For the dissolution of the sample FeSAsOH–1 [Fe(SO4 )0.27 (AsO4 )0.73 (OH)0.27 ·0.26H2 O] at 25–45°C and initial pH 2, all constituents preferred to be dissolved in the order of AsO4 3− > SO4 2− > Fe 3+ in 1–3 h, in the order of SO4 2− > AsO4 3− > Fe 3+ from 1–3 h to 12–24 h, and finally in the order of SO4 2− > Fe 3+ > AsO4 3− . The released iron, sulfate, and arsenate existed dominantly as Fe 3+ /Fe(OH) 2+ /FeSO4 +, HSO4 − /SO4 2− /FeSO4 +, and H3 AsO4 0 /H2 AsO4 −, respectively. The higher initial pHs (6 and 10) could obviously inhibit the release of Fe 3+ from solid into solution, and the solid components were released in the order of SO4 2− > AsO4 3− > Fe 3+ . The crystal tops were first dissolved, and the crystal surfaces were gradually smoothed/rounded until all edges and corners disappeared. The dissociations were restricted by the Fe-O(H) breakdown in the FeO6 octahedra and obstructed by the OH − and AsO4 tetrahedra outliers; the lowest concentration of the dissolved arsenic was 0.045 mg/L. Based on the dissolution experiment at 25°C and pH 2, the solubility products ( K sp ) for the basic ferric sulfate-arsenate [Fe(SO4 )0.27 (AsO4 )0.73 (OH)0.27 ·0.26H2 O], which are equal to the ion activity products (logˍIAP) at equilibrium, were calculated to be -23.04 ± 0.01 with the resulting Gibbs free energies of formation (Δ G f o ) of −914.06 ± 0.03 kJ/mol.